Die houding van die Open baring van Johannes teenoor kultuur - Engelbrecht, J. J. (Hervormde teologiese studies, 1996)
The attitude of the Apocalypse of John towards culture. The last book of the Bible was not written in the first instance to say something about the believer's attitude towards and use of culture as such. However, between the lines important information is to be found. Those who really believe in Him who is proclaimed in this book do not need to exchange the culture of their people for the culture of another group. It should always be borne in mind, however; that if a certain aspect of one's culture is contrary to the gospel or is a hindrance to the passing on of the gospel to all human beings, the gospel should have priority over one's beloved culture and traditions.